International Political Risk Management : Looking to the Future - Moran, Theodore (Washington, DC: World Bank, 2012)
This publication is the third in a series of volumes based on the Multilateral Investment Guarantee Agency-Georgetown University Symposium in International Political Risk Management. Like its predecessors, this volume offers expert assessments of needs, trends, and challenges in the international political risk insurance industry. These assessments come from a dozen senior practitioners from the investor, financial, insurance, broker, and analytical communities. The volume leads off by examining the lessons that can be learned from recent investment losses, insurance claims, and arbitrations. It then turns to consider what the future may hold for coverage of project finance projects in emerging markets as well as recent public-private collaboration trends in the issuance of political risk insurance. It concludes by reconsidering both old and new political risk insurance products and innovations that seek to expand the tools that international investors can utilize to mitigate political risk abroad.